2014
DOI: 10.2172/1378055
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Oxidative Stability of Alkaline Soluble, Non-Pertechnetate Technetium

Abstract: Tc(CO) 3 ] + /gluconate complex was considerably slower in the supernatant simulant than in the simple 5 M NaNO 3 /0.5 M NaOH/0.5 M NaGluconate solution. 4. These results indicate that a carbonyl complex is a viable candidate for the source of non-pertechnetate in tank waste. As indicated, testing has identified a range of conditions under which a significant portion of the carbonyl complex is stable for extended periods of time. Preliminary studies have shown a viable route for the formation of this complex u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…Previous analysis of the SY-101 and SY-103 tank waste samples provided strong evidence that non-pertechnetate can be comprised of [Tc(CO) 3 ] + complexes containing Tc in oxidation state +1 (Lukens et al 2004). During the last two years, our team has expanded this work and demonstrated that high-ionic-strength solutions typifying tank waste supernatants promote oxidative stability of the [Tc(CO) 3 ] + species (Rapko et al 2013;Levitskaia et al 2014). It also was observed that high-ionic-strength alkaline matrices stabilize Tc(VI) and potentially Tc(IV) oxidation states, particularly in presence organic chelators, suggesting that the relevant Tc compounds can serve as important redox intermediates facilitating the reduction of Tc(VII) to Tc(I).…”
Section: Discussionmentioning
confidence: 86%
“…Previous analysis of the SY-101 and SY-103 tank waste samples provided strong evidence that non-pertechnetate can be comprised of [Tc(CO) 3 ] + complexes containing Tc in oxidation state +1 (Lukens et al 2004). During the last two years, our team has expanded this work and demonstrated that high-ionic-strength solutions typifying tank waste supernatants promote oxidative stability of the [Tc(CO) 3 ] + species (Rapko et al 2013;Levitskaia et al 2014). It also was observed that high-ionic-strength alkaline matrices stabilize Tc(VI) and potentially Tc(IV) oxidation states, particularly in presence organic chelators, suggesting that the relevant Tc compounds can serve as important redox intermediates facilitating the reduction of Tc(VII) to Tc(I).…”
Section: Discussionmentioning
confidence: 86%
“…It is significant that only about 5-10% of total Tc present in the sample got oxidized to TcO 4 in 30 days ( Figure 5; green trace [second from bottom]) as determined based on the integration of signal intensity from a TcO 4 standard of known concentration. This is in contrast to the Tc(I) [Tc(CO) 3 ] + species, which undergo fast oxidative hydrolysis to form TcO 4 in aqueous solutions with low ionic strength (Rapko et al 2013;Levitskaia et al 2014). When the yellow reaction precipitate was dissolved in 5 M NaNO 3 , it demonstrated similar but significantly less intense color change from yellow to red.…”
Section: Characterization Of the [Tc(co) 2 (No)] 2+ Products In The Rmentioning
confidence: 92%
“…It was recently proposed based on the x-ray absorption studies of the actual SY-101 and SY-103 tank waste supernatants that non-pertechnetate species are the derivatives of low-valent Tc(I) carbonyl moiety and derived from fac-[Tc(CO) 3 ] + , 2 (Lukens et al 2004). Recent work by our group has significantly expanded this hypothesis, demonstrating that Tc(I) carbonyl compounds can be generated from reduction of TcO 4 in simulated Hanford tank waste in the presence CO at elevated temperature (Levitskaia et al 2014), and ongoing monitoring of these samples indicates long-term stability of Tc(I) carbonyl non-pertechnetate 3 . These results are consistent with the proposal that [Tc(CO) 3 ] + species can be present in the Hanford tank waste and suggest that the low Tc(I) oxidation state is stabilized by the π-accepting ability of the CO ligands.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations